Metallocene-catalyzed polymers : materials, properties, processing & markets - Benedikt, George M.; Goodall, Brian L. (Plastics Design Library., 1998)
Offers insights into applications in automotive components, food packaging, insulating films, non-woven fabrics, and medical markets, among others.